An unusual cause for Coffin–Lowry syndrome: Three brothers with a novel microduplication in RPS6KA3. Issue 12 (12th September 2019) - Castelluccio, Valerie J.; Vetrini, Francesco; Lynnes, Ty; Jones, Julie; Holloway, Lynda; Belonis, Alyce; Breman, Amy M.; Graham, Brett H.; Sapp, Katherine; Wilson, Theodore; Schwartz, Charles E.; Pratt, Victoria M.; et al.
Abstract: Coffin–Lowry syndrome (CLS) is a rare X‐linked disorder characterized by moderate to severe intellectual disability, hypotonia, craniofacial features, tapering digits, short stature, and skeletal deformities. Using whole exome sequencing and high‐resolution targeted comparative genomic hybridization array analysis, we identified a novel microduplication encompassing exons five through nine of RPS6KA3 in three full brothers. Each brother presented with intellectual disability and clinical and radiographic features consistent with CLS. qRT‐PCR analyses performed on mRNA from the peripheral blood of the three siblings revealed a marked reduction of RPS6KA3 levels suggesting a loss‐of‐function mechanism. PCR analysis of the patients' cDNA detected a band greater than expected for an exon 4–10 amplicon, suggesting this was likely a direct duplication that lies between exons 4 through 10, which was later confirmed by Sanger sequencing. This microduplication is only the third intragenic duplication of RPS6KA3, and the second and smallest reported to date thought to cause CLS. Our study further supports the clinical utility of methods such as next‐generation sequencing and high‐resolution genomic arrays to detect small intragenic duplications. These methods, coupled with expression studies and cDNA structural analysis have the capacity to confirm the diagnosis of CLS in these rare cases.